2022
DOI: 10.3390/cells11223577
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis Identifies MNX1 and Associated Antisense Transcripts as Biomarkers for Cancer

Abstract: The identification of diagnostic and prognostic biomarkers is a major objective in improving clinical outcomes in cancer, which has been facilitated by the availability of high-throughput gene expression data. A growing interest in non-coding genomic regions has identified dysregulation of long non-coding RNAs (lncRNAs) in several malignancies, suggesting a potential use as biomarkers. In this study, we leveraged data from large-scale sequencing projects to uncover the expression patterns of the MNX1 gene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The pan-cancer analysis is a comprehensive and systematic approach to investigating and assessing the function and mechanism of a specific gene in tumorigenesis. Using the TCGA database, several genes were identified that may have a role in human cancers, such as FGL1 [30], CARM1 [31], CBX [32], LCK [33], and MNX1 [34]. In the present study, we conducted a systematic analysis of SKP2 expression across a variety of tumor forms, and the results revealed that practically most tumor types overexpressed SKP2 ).…”
Section: Discussionmentioning
confidence: 74%
“…The pan-cancer analysis is a comprehensive and systematic approach to investigating and assessing the function and mechanism of a specific gene in tumorigenesis. Using the TCGA database, several genes were identified that may have a role in human cancers, such as FGL1 [30], CARM1 [31], CBX [32], LCK [33], and MNX1 [34]. In the present study, we conducted a systematic analysis of SKP2 expression across a variety of tumor forms, and the results revealed that practically most tumor types overexpressed SKP2 ).…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, MNX1 encodes a transcription factor (HB9) that contains a homeodomain. The overexpression of MNX1 has been reported in many cancers (prostate, colon, liver, breast and bladder cancer, glioma and pancreatic progenitor tumors and acute myeloid leukemia) and has been suggested as potential diagnostic and prognostic biomarker [36,37]. Upregulation of MNX1 stimulates the Wnt/β-catenin signaling and via expression of downstream genes c-Myc and CCND1, hence plays a vital role in CRC progression [38].…”
Section: Discussionmentioning
confidence: 99%